Treatment of male rats with finasteride, an inhibitor of 5alpha-reductase enzyme, induces long-lasting effects on depressive-like behavior, hippocampal neurogenesis, neuroinflammation and gut microbiota composition. (January 2019) - Diviccaro, Silvia; Giatti, Silvia; Borgo, Francesca; Barcella, Matteo; Borghi, Elisa; Trejo, José Luis; Garcia-Segura, Luis Miguel; Melcangi, Roberto Cosimo
Highlights: One month of finasteride withdrawal induced depressive-like behavior. Decrease of neurogenesis occurred after one month of finasteride withdrawal. GFAP immunoreactivity was increased after one month of finasteride withdrawal. Finasteride treatment and its withdrawal induced neuroinflammation in hippocampus. Gut microbiota composition was affected by finasteride treatment and its withdrawal. Abstract: Persistent alteration of plasma neuroactive steroid levels associated with major depression has been recently reported in men after the suspension of the treatment for androgenetic alopecia with finasteride, an inhibitor of the enzyme 5alpha-reductase. Observations in male rats confirmed persistent alterations in neuroactive steroid levels also in the brain. In the present study, we have ascertained possible effects on depressive-like behavior, neurogenesis, gliosis, neuroinflammation and gut microbiota in male rats after subchronic treatment for 20 days with finasteride and after one month of its withdrawal. At the end of treatment there was an increase in the number of pH3 immunoreactive cells in the subgranular zone of the dentate gyrus together with an increase in the mRNA levels of TNF-α in the hippocampus. By one month after the end of finasteride treatment, rats showed depressive-like behavior coupled with a decrease in the number of pH3 immunoreactive cells in the subgranular zone of the dentate gyrus, a decrease in granule cell density in the granule cell layer and an increase in the number of GFAP immunoreactive astrocytes in the dentate gyrus. Finally, alteration of gut microbiota (i.e., an increase in Bacteroidetes phylum and in Prevotellaceae family at the end of the treatment and a decrease in Ruminococcaceae family, Oscillospira and Lachnospira genus at the end of the withdrawal period) was detected. In conclusion, finasteride treatment in male rats has long term effects on depressive-like behavior, hippocampal neurogenesis and neuroinflammation and gut microbiota composition.